Ação Larvicida de espécies da família piperaceae em anopheles sp e Culex quinquefasciatus (DIPTERA: CULICIDAE) - Corrêa, Rachel Geber (2007)
Extracts from eight species of the Piperaceae family were utilized to evaluate the larvicidal activity against 3rd instar larvae 3rd of Culex quinquefasciatus e Anopheles sp. Plant material that belongs to the Piper genera were collected from two places: Piper hostmanianum, P. dilatatum e P. tuberculatum were collected at the main campus of INPA – Instituto Nacional de Pesquisas da Amazônia, in Manaus, capital of the Amazonas State. The remaining species P. amapense, P. cyrtopodon, P. capitarianum, P. baccans e P. erectipillum were collected at the Adolpho Ducke reserve located at peripheric area of Manaus. The extracts were obtained from a standardized procedure that involved the extraction of the dried material in a Soxhlet apparatus for 18 h with methanol replacing the solvent every 6 hours. The evaluated extracts were obtained from different parts of plants – fruits, leaves, stems and roots. The biologic tests were made in rejoinders of 3 inside dismissable 50 mL cups containing 10 mL of distilled water within variable concentrations of 0,008 to 1000 μg/mL by making the mortality reading in 24 h. The most active extract was fractioned by the means of chromatographic techniques and the biomonitoring test enabled to isolate the main pelitorina e piplartina components that were identified by the means of monodimensioned nuclear magnetic resonance (RMN 1H e 13C). The studies of the larvicidal activity with the fractions and the isolated substance indicated a sinergystic effect among them. There were also registered external and behavior morphologic alterations of the 3rd instar larvae of A. nuneztovari in contact with the hexanic and chloroformic fruit extracts of Piper tuberculatum.